13th International Conference on Aluminum Alloys (ICAA 13) Conference Proceedings - Weiland, Hasso; Rollett, Anthony; Cassada, William (The Minerals, Metals & Materials Series,, 2016)
This is a collection of papers presented at the 13th International Conference on Aluminum Alloys (ICAA-13), the premier global conference for exchanging emerging knowledge on the structure and properties of aluminum materials. The papers are organized around the topics of the science of aluminum alloy design for a range of market applications; the accurate prediction of material properties; novel aluminum products and processes; and emerging developments in recycling and applications using both monolithic and multi-material solutions.